EFFECT OF PLANT ALKALOIDS ON MITOCHONDRIAL MEMBRANE PERMEABILITY (Scientific journal of the Fergana State University, 2023)
The study of the physicochemical properties of mitochondrial membranes shows that its inner membrane selectively allows certain compounds to pass through, for example, drugs. It is necessary to take into account the influence of pharmacological agents on the functional parameters of mitochondria not only from a toxicological, but also from a therapeutic point of view. Potential targets for several pharmacological agents have been identified at the mitochondrial level.